The analysis of factors influencing loan losses provision of China's commercial banks - Bian, Shuo (2017)
In order to solve the problem of non-performing loans, China's banking industry should correctly prepare for the loss of loans. In this paper, the factors affecting the loan loss are the main factors in the development of China's banking sector. Analyzed. In this paper, the panel data of 15 banks in 2011-2016 were analyzed, and the GMM regression analysis was carried out, and the cost was obtained. The efficiency factor was obtained by SFA function analysis. Through the generalized two-step GMM analysis, The variables that affect the loan loss preparation, and the extent of the impact, and makes recommendations for the conclusions drawn.